Mass closure vs. layer-by-layer closure of transverse laparotomy in children: a randomized trial with ultrasound and elastography outcomes - Shehata, Mohamed Ali; Khirallah, Mohammad Gharieb; Kurdi, Mazin; Abdelwahab, Shaimaa Abdelmonem; Elkhouly, Radwa; Gado, Suzan Ezzat (Frontiers in Pediatrics, 2025)
Backgroundtransverse laparotomy incision presents a common and widely used one in infants and children. The fascial incision is either closed in one mass or layer-by-layer closure. Both methods nearly have the same outcomes. This study randomly compared the two main techniques of closure of the transverse laparotomy incision, regarding clinical, sonographic, and elastrographic changes.MethodsThis trial included infants and children who were subjected to a transverse upper abdominal laparotomy incision. Patients whose muscle sheath complex defects were closed using the mass closure technique were allotted to Group A. Patients whose defects were closed using the layer-by-layer closure technique were allotted to Group B. The wounds were subjected to musculoskeletal ultrasound and elastography examination.ResultsThe age was 22.3 months and 22.5 months in Group A and Group B, respectively. Fatty infiltration >30% but <40% was observed in 35 cases in Group A and 15 cases in Group B, (p = 0.04). The 20%–40% fibrosis in the muscle sheath complex observed in 33 cases in Group A and 9 cases in Group B, (p = 0.02). During the last follow-up examination at the end of first year, the shear wave speed was 6.4 m/s in Group A and 3.1 m/s in Group B (p = 0.05).ConclusionMass closure resulted in significantly higher stiffness and fatty infiltration of the muscle sheath complex compared to layer-by-layer closure, as shown by elastography and ultrasound. These biomechanical alterations may predispose to increased long-term risk of incisional hernia despite comparable short-term outcomes.